Evangelium in Silicio: A Systematic Literature Review on AI-Enhanced Catechesis Methods for Generation Z Catholics - Fransiskus Janu Hamu; Yustinus Dwi Andriyanto (Sepakat : Jurnal Pastoral Kateketik, 2024)
This research analyzes the potential integration of Artificial Intelligence (AI) in Catholic catechesis for Generation Z through a systematic literature review of 98 articles published between 2015-2024. Using the PRISMA approach and three-level thematic analysis, this study identifies significant transformations in digital catechesis methods, focusing on three main areas: personalization of faith formation, digital contextualization, and AI integration in spiritual assessment. Results show improvements in doctrinal understanding and sacramental participation when AI is appropriately implemented. The digital catechesis integrity and adaptive learning pathways frameworks provide guidance for implementation that balances technological innovation with fidelity to the Magisterium. This study contributes to developing catechesis models that are responsive to Generation Z's needs while maintaining the integrity of Catholic teaching.